2023
DOI: 10.1128/spectrum.05340-22
|View full text |Cite
|
Sign up to set email alerts
|

Diversity Analysis of Tick-Borne Viruses from Hedgehogs and Hares in Qingdao, China

Abstract: Thirty-six strains of 10 RNA viruses belonging to 4 viral families, including 3 viruses of Iflaviridae , 4 viruses of Phenuiviridae , 2 viruses of Nairoviridae , and 1 virus of Chuviridae , were identified from five tick species in Qingdao, China. A diversity of tick-borne viruses from hares and hedgehogs in Qingdao was found in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…There are additional noteworthy phenomena that deserve attention in this study. Consistent with previous studies, we observed that newly tick-borne viruses in China were closely related to strains found in Japan [ 47 ]. We also identified some viruses, such as YGTV, that were closely related to Russian strains.…”
Section: Discussionsupporting
confidence: 91%
“…There are additional noteworthy phenomena that deserve attention in this study. Consistent with previous studies, we observed that newly tick-borne viruses in China were closely related to strains found in Japan [ 47 ]. We also identified some viruses, such as YGTV, that were closely related to Russian strains.…”
Section: Discussionsupporting
confidence: 91%